Surrounding rock pressure calculation based on time functions and stress release rate determination of deep soft rock tunnel: taking Zhonghe Tunnel as an example - Ding, Xiao; Deng, Xianghui; Zhang, Xuan; Wang, Rui (Frontiers in Earth Science, 2023)
On the basis of the Zhonghe Tunnel project of the An-Lan Expressway, the objective of this study was to determine the appropriate method of calculating the steel arch load and stress release rate during numerical simulation. First of all, based on the monitoring results of six similar tunnel sections where the surrounding rock exerts pressure on the steel arch, using time functions, the rock pressure time history curve could be fitted, two formulas for calculating stable rock pressure in deep tunnels were compared, and the calculation model suitable for the Zhonghe Tunnel project was constructed. Then, a simulation of the Zhonghe Tunnel was performed using Flac3D, and stress release was simulated using the Mana method. By comparing the surrounding rock characteristic curves and the initial support characteristic curves under different stress release rates, the impact pattern of the stress release rate on the support load was summarized, and an appropriate excavation stress release rate was determined based on the stable rock pressure value calculation. It was found that the Zhonghe Tunnel rock pressure calculation model could better depict the change in rock pressure over time based on the empirical formula and Weibull time function. A prediction of the steel arch load of the Zhonghe Tunnel could be made using this method, and the stress release rate of the numerically simulated rock excavation was determined to be 0.5. This study thus provides a basis for the future internal force analysis and support parameter design of support systems.